Specialists leave fewer descendants within a region than generalists. Issue 2 (22nd August 2012) - Ozinga, Wim A.; Colles, Audrey; Bartish, Igor V.; Hennion, Françoise; Hennekens, Stephan M.; Pavoine, Sandrine; Poschlod, Peter; Hermant, Marie; Schaminée, Joop H. J.; Prinzing, Andreas; Cardillo, Marcel
Abstract Aim Current conservation biology suggests that across ecological time‐scales specialist species existing in the recent past have left on average fewer descendant populations today than generalist species. Conversely, the speciation literature suggests that on an evolutionary time‐scale specialists leave as many or more descendant lineages as generalists, i.e. they have high rates of global diversification. This begs the question: which of these two processes has more influence on the regional scale, i.e. do specialists leave more or fewer descendants than generalists within a region? Location The flora of the Netherlands. Methods We quantified niche volume of 707 plant species from coexistence data and ecological indicator values and used sister taxon comparisons to compare specialist and generalist sister taxa for the relative numbers of descendants across three temporal scales: ecological, microevolutionary and macroevolutionary. Results We show, first, that specialist species are more likely to be currently declining, i.e. to leave only few descendant populations. Second, specialists are less likely to be currently diversifying into intra‐specific taxa. Finally, most specialist clades left fewer descendant species within a region than their generalist sister clades. These results were consistent across sublineages, unbiased by geographic sampling of lineages and environments, and held after accounting for species life histories. Differences between specialist and generalist sister clades increased with clade age, suggesting that they reflect differences in rates at which specialists left descendants (rather than differences in ecological limits to the numbers of specialists and generalists). Main conclusions Specialists left only few descendants within a region (i.e. the Netherlands), both at ecological, microevolutionary and macroevolutionary scales. While specialists may leave numerous evolutionary descendants at a global scale, these might be absent from most regions. Humans, by threatening specialist species, may hence further accelerate biotic homogenization with descendants of generalist lineages proliferating within regions while specialist lineages disappear.